Schedule of Classes, Spring 2011 - University of Wisconsin-Milwaukee. Department of Enrollment Services (My University, 2011)
PDF version of the UW-Milwaukee Schedule of Courses for the Spring 2011 term. Includes registration policies and lists of available classes during this term.